Proteomic responses of two spring wheat cultivars to the combined water deficit and aphid (Metopolophium dirhodum) treatments - Kosová, Klára; Vítámvás, Pavel; Skuhrovec, Jiří; Vítámvás, Jan; Planchon, Sébastien; Renaut, Jenny; Saska, Pavel (Frontiers in Plant Science, 2022)
In the field, plants usually have to face the combined effects of abiotic and biotic stresses. In our study, two spring wheat cultivars Septima and Quintus were subjected to three water regimes (70, 50, 40 % soil water capacity SWC), aphid (Metopolophium dirhodum) infestation or the combination of both stresses, i.e., water deficit (50, 40 % SWC) and aphids. The study has a 2×3×2 factorial design with three biological replicates. Our previous study (Saska et al. 2022 J. Pest Sci., doi: 10.1007/s10340-022-01514-3) investigated plant morphophysiological characteristics and aphid life table. In the present study, the results of proteomic analysis using 2D-DIGE followed by MALDI-TOF/TOF protein identification are presented. Water deficit, but also aphid infestation led to alterations in 113 protein spots including proteins assigned to a variety of biological processes ranging from signalling via energy metabolism, redox regulation, stress and defense responses to secondary metabolism indicating a long-term adaptation to adverse conditions. The absence of specific proteins involved in plant response to herbivorous insects indicates a loss of resistance to aphids in modern wheat cultivars during the breeding process and is in accordance with “plant vigour hypothesis“. Septima revealed enhanced tolerance with respect to Quintus as indicated by higher values of morphophysiological characteristics (fresh above-ground biomass, leaf length, osmotic potential per full water saturation) and relative abundance of proteins involved in mitochondrial respiration and ATP biosynthesis.